Heart Disease of Children - Halimovich, Mavlonov Namoz (American Journal of Biomedicine and Pharmacy, 2024)
Arrhythmia is one of the most common diseases of the cardiovascular system among children and adolescents. They appear in heart failure. Arrhythmia is characterized by changes in the frequency, regularity and sequence of heart contractions. In a broader sense, arrhythmia is any deviation of the heart rhythm from the norm.